The Use of the” My Point of View " Method In The Formation Of Reading Comprehension Skills Of Primary School Students (Eurasian Research Bulletin, 2024)
The article describes the effectiveness of using the “My point of view” method in the formation of reading comprehension skills of Primary School students, encouraging students to comprehensively think and draw important conclusions about the text.